Decay of enveloped SARS-CoV-2 and non-enveloped PMMoV RNA in raw sewage from university dormitories - Li, Ye; Ash, K. T.; Joyner, Dominique C.; Williams, Daniel E.; Alamilla, I.; McKay, P. J.; Iler, C.; Green, B. M.; Kara-Murdoch, F.; Swift, C. M.; Hazen, Terry C. (Frontiers in Microbiology, 2023)
Although severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA has been frequently detected in sewage from many university dormitories to inform public health decisions during the COVID-19 pandemic, a clear understanding of SARS-CoV-2 RNA persistence in site-specific raw sewage is still lacking. To investigate the SARS-CoV-2 RNA persistence, a field trial was conducted in the University of Tennessee dormitories raw sewage, similar to municipal wastewater. The decay of enveloped SARS-CoV-2 RNA and non-enveloped Pepper mild mottle virus (PMMoV) RNA was investigated by reverse transcription-quantitative polymerase chain reaction (RT-qPCR) in raw sewage at 4 and 20°C. Temperature, followed by the concentration level of SARS-CoV-2 RNA, were the most significant factors that influenced the first-order decay rate constants (k) of SARS-CoV-2 RNA. The mean k values of SARS-CoV-2 RNA were 0.094 day-1 at 4°C and 0.261 day-1 at 20°C. At high, medium, and low concentration levels of SARS-CoV-2 RNA, the mean k values were 0.367, 0.169, and 0.091 day−1, respectively. Furthermore, there was a statistical difference between the decay of enveloped SARS-CoV-2 and non-enveloped PMMoV RNA at different temperature conditions. The first decay rates for both temperatures were statistically comparable for SARS-CoV-2 RNA, which showed sensitivity to elevated temperatures but not for PMMoV RNA. This study provides evidence for the persistence of viral RNA in site-specific raw sewage at different temperature conditions and concentration levels.